Adherence level and Determinants of Non-Adherence of Antiretroviral Therapy among people living with HIV/AIDS Attending Aminu Kano Teaching Hospital, Kano, Nigeria - Busari, Abdulwasiu A.; Oreagba, Ibrahim; Abdullahi, Musa; lshola, lsmaii; Usman, Sikiru; Olayerni, Sunday (The Nigerian Journal of Pharmacy, 2013)
Click the download to preview.